Randomized, Open Label, Active Controlled Comparative Study to Assess Safety, Efficacy of Mometasone & Formoterol Versus Fluticasone & Formoterol Dry Powder Inhaler in Treatment of Mild to Moderate Persistent Asthma - Parasuramalu B G; Sathish Chandra MR; Huliraj N; Giriyanna Gowda; Gangaboraiah (Medsci Publications, 2015)
Background: This study conducted to assess and compare the safety and efficacy of Mometasone & Formoterol versus Fluticasone & Formoterol. in patients with mild to moderate persistent asthma on symptom control and rescue medication usage. Method: The present study was conducted during March 2011 to February 2012. 120 patients were randomized in to two groups and were given Mometasone & Formoterol to group 1 and Fluticasone & Formoterol to group 2 for 12 weeks. Result: Out of 60 patients recruited in each group 7 were lost to follow up in Fluticasone group and 4 in Mometasone group. Out of 53 patients in Fluticasone group, 11 developed adverse reactions. Whereas in Mometasone group out of 56 patients- 7 developed adverse reactions. The overall improvement in Spi- rometry parameters was better in Mometasone group com- pared to Fluticasone which was not statistically significant suggesting both were equally efficacious. There was reduction in dosage of rescue medication used from baseline to the end of 12 weeks in Mometasone group compared to Fluticasone group. Conclusion: Both combinations were safe and equally effica- cious in treating mild to moderate persistent asthma patients.